2019
DOI: 10.14520/adyusbd.490598
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of First Grade Turkish Language (First Reading-Writing) Curriculum

Abstract: In this study, it was aimed to evaluate the first grade Turkish language curriculum. In the study, case study was used in qualitative research methods. The data of the study was collected by observation and interview form. In the selection of the observing school, sampling of the typical situation was taken by taking the student profile and purpose sampling methods was used in the determination of the interviewed teachers. Data obtained by interview and observation were analyzed by descriptive analysis techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…These studies were generally utilized quantitative research methods or the interview technique among the qualitative research methods. In addition, in their study entitled "Evaluation of First Grade Turkish Language (First Reading-Writing) Curriculum", Aslan and Altunova (2019) used interview and observation techniques in tandem. However, the study was found to make evaluations only concerning the process of first reading and writing.…”
Section: Introductionmentioning
confidence: 99%
“…These studies were generally utilized quantitative research methods or the interview technique among the qualitative research methods. In addition, in their study entitled "Evaluation of First Grade Turkish Language (First Reading-Writing) Curriculum", Aslan and Altunova (2019) used interview and observation techniques in tandem. However, the study was found to make evaluations only concerning the process of first reading and writing.…”
Section: Introductionmentioning
confidence: 99%